2012
DOI: 10.1002/elps.201200225
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of a COP‐based microfluidic chip: Chronoamperometric detection of Troponin T

Abstract: This work demonstrates the design and fabrication of an all cyclo-olefin polymer based microfluidic device capable of capturing magnetic beads and performing electrochemical detection in a series of gold electrodes. The size of chip is of a microscope slide and features six independent measuring cells for multianalyte detection purposes. The aim of this work is to show that rapid prototyping techniques can be instrumental in the development of novel bioassays, particularly in clinical diagnosis applications. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The great analytical performance of the magnetoimmunosensor, remarkably better than those reported before for other immunosensors (Table 4), the use of mass‐produced electrochemical transducers, together with meeting the criteria required for the unequivocal diagnosis of AMI, make the developed magnetoimmunosensor a useful and affordable analytical tool for clinical diagnosis and the development of POC devices for on‐site analysis of necrosis cardiac proteins. Following this work, an all cyclo‐olefin polymer (COP) based disposable microfluidic device, which is capable of capturing MBs and perform electrochemical detection in a series of Au electrodes, has been fabricated 36. The microfluidic device (Figure 6) was successfully applied to the determination of cTnT in the clinical relevant range from 0.05 to 1.0 ng mL −1 with a LOD of 0.03 ng mL −1 in buffer solutions.…”
Section: Electrochemical Biosensors For Cardiovascular Markersmentioning
confidence: 99%
“…The great analytical performance of the magnetoimmunosensor, remarkably better than those reported before for other immunosensors (Table 4), the use of mass‐produced electrochemical transducers, together with meeting the criteria required for the unequivocal diagnosis of AMI, make the developed magnetoimmunosensor a useful and affordable analytical tool for clinical diagnosis and the development of POC devices for on‐site analysis of necrosis cardiac proteins. Following this work, an all cyclo‐olefin polymer (COP) based disposable microfluidic device, which is capable of capturing MBs and perform electrochemical detection in a series of Au electrodes, has been fabricated 36. The microfluidic device (Figure 6) was successfully applied to the determination of cTnT in the clinical relevant range from 0.05 to 1.0 ng mL −1 with a LOD of 0.03 ng mL −1 in buffer solutions.…”
Section: Electrochemical Biosensors For Cardiovascular Markersmentioning
confidence: 99%
“…Moreover, Abad et al have demonstrated that cTnT can be determined in the range of 0.05-1.0 ng/mL using a cyclo-olefin polymer based microfluidic device for capturing magnetic beads and performing electrochemical detection (63). A detection limit of 2 pg/mL for cTnI was reached by using nanoparticle-based electrochemiluminescence immunosensor labels in a high sensitive sandwich-type immunoassay (64).…”
Section: Sst2 Gdf-15 Hstn Imentioning
confidence: 99%
“…Well-developed photolithographybased methods exist to pattern gold or other conductive materials onto flat surfaces, which can be used as the bottom substrate upon which microfluidic channels are bonded. The most commonly used techniques combine photolithography with either etching or lift off [18,19]. In etching, the conductive material is deposited first, and then photoresist is applied on top and patterned, acting as a protective mask.…”
Section: Introductionmentioning
confidence: 99%